Introduction to Bureaucracy - Mises, Ludwig von (2015)
In this article, the author criticizes bureaucratism, then shows how it is rejected by the citizens of the United States and makes a logical correlation between bureaucracy and the totalitarian regimes that it nourishes. He argues on unanimity with regard to the distinction between two contrary methods of doing things: the way of the citizens and the manner how government agencies and municipalities are managed. Finally, he sustains that bureaucracy can only be understood by contrasting it with the operation of the profit motive as it functions in the capitalist market society.